Facilitators and barriers to implementing an acute geriatric community hospital in the Netherlands: a qualitative study. (27th January 2023) - Ribbink, Marthe E; de Vries-Mols, Wieteke C B M; MacNeil Vroomen, Janet L; Franssen, Remco; Resodikromo, Melissa N; Buurman, Bianca M
Abstract: Background: there is a trend across Europe to enable more care at the community level. The Acute Geriatric Community Hospital (AGCH) in the Netherlands in an acute geriatric unit situated in a skilled nursing facility (SNF). It provides hospital-level care for older adults with acute medical conditions. The aim of this study is to identify barriers and facilitators associated with implementing the AGCH in a SNF. Methods: semi-structured interviews ( n = 42) were carried out with clinical and administrative personnel at the AGCH and university hospital and stakeholders from the partnering care organisations and health insurance company. Data were analysed using thematic analysis. Results: facilitators to implementing the AGCH concept were enthusiasm for the AGCH concept, organising preparatory sessions, starting with low-complex patients, good team leadership and ongoing education of the AGCH team. Other facilitators included strong collaboration between stakeholders, commitment to shared investment costs and involvement of regulators. Barriers to implementation were providing hospital care in an SNF, financing AGCH care, difficulties selecting patients at the emergency department, lack of protocols and guidelines, electronic health records unsuited for hospital care, department layout on two different floors and complex shared business operations. Furthermore, transfer of acute care to the community care meant that some care was not reimbursed. Conclusions: the AGCH concept was valued by all stakeholders. The main facilitators included the perceived value of the AGCH concept and enthusiasm of stakeholders. Structural financing is an obstacle to the expansion and continuation of this care model.